(untitled) (Historia, 2021)
For the ordinary sailor in the days of company monopoly trade with the Far East a life afloat was arduous, often dangerous and generally lacking in creature comforts. The food was not always wholesome, the water-supply sometimes tainted and the crews’ quarters dank, dark, cramped and noisome. Despite efforts when weather per-mitted to fumigate the ships and to swab the lower decks with vinegar, cleanliness was not a notable feature aboard the East Indiamen of any of the competing national companies. Erik Gobel has recently given us a striking example from the records of the Danish Asiatic Company. When the vessel Kronprinsessen af Danmark was crossing the Indian Ocean on her uncompleted homeward run in 1753, the reward of a tot of brandy was offered to any man who collected 1 000 cockroaches. In thirty-eight days, 38 250 of these omnivorous insects were caught by diligent searchers.